2012
DOI: 10.3109/08958378.2012.731093
|View full text |Cite|
|
Sign up to set email alerts
|

Involvement of TLR2 and TLR4 and Th1/Th2 shift in inflammatory responses induced by fine ambient particulate matter in mice

Abstract: Epidemiologic studies have reported the association between fine particles (aerodynamic diameter ≤ 2.5 μm; PM2.5) and health effects, but the immunological mechanisms are not clear. To investigate the dose and time-dependent role of toll-like receptor (TLR) and Th1/Th2 shift in local and systemic inflammation induced by PM2.5, mice were subjected to intratracheal instillation of 2.5, 5, or 10 mg/kg PM2.5 in this study. After 24 h, 72 h, 7 days, and 14 days, mice were sacrificed to measure TLR2 and TLR4 express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
46
0
5

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(57 citation statements)
references
References 42 publications
6
46
0
5
Order By: Relevance
“…Here, we confirmed that DEPs triggers TLR4, and the NFκB pathway in both pineal microglia and alveolar macrophages. As previously observed following LPS exposure, the DEP‐induced blockade of microglial TNF production triggered TNFR1 in pinealocytes, blocking pineal melatonin synthesis.…”
Section: Discussionsupporting
confidence: 74%
“…Here, we confirmed that DEPs triggers TLR4, and the NFκB pathway in both pineal microglia and alveolar macrophages. As previously observed following LPS exposure, the DEP‐induced blockade of microglial TNF production triggered TNFR1 in pinealocytes, blocking pineal melatonin synthesis.…”
Section: Discussionsupporting
confidence: 74%
“…35 This fraction was chosen because the size of <2.5 μm in diameter allows the particles to travel via the airways into the alveoli. The dose chosen was at half the concentration of the dose reported to induce significant airway inflammation using PM 2.5 sampled in New York City, 35 Beijing, 36 and Baltimore. Antigen immunization and exposure to antigen and PM Animals were primed and challenged with antigen as described elsewhere 17,18 and schematically presented in Figure 2A.…”
Section: Urban Pm 18mentioning
confidence: 99%
“…The dose of PM2.5 that we used was at half the concentration of the dose reported to induce significant airway inflammation using PM2.5 sampled in New York City [38], Beijing [39], and Baltimore [40]. When given without OVA, PM2.5 at the 25 μg/50 μL dose did not elicit significant airway inflammation or vascular remodeling [7].…”
Section: Methodsmentioning
confidence: 99%